Unveiling the extreme environmental radioactivity of cryoconite from a Norwegian glacier - Łokas, Edyta; Wachniew, Przemysław; Baccolo, Giovanni; Gaca, Paweł; Janko, Karel; Milton, Andrew; Buda, Jakub; Komędera, Kamila; Zawierucha, Krzysztof (Science of The Total Environment, 2022)
This study is a first survey of the occurrence of artificial (137Cs, 241Am, 207Bi, Pu isotopes) and natural (210Pb, 228Ac, 214Bi, 40K) radionuclides in cryoconite from a Scandinavian glacier. Cryoconite samples were collected before (12 samples) and after (5 samples) a rainfall event. The concentrations of radionuclides in cryoconite samples from the Blåisen Glacier are compared with data from the Arctic and Alpine glaciers. Cryoconite samples from the studied glacier had extremely high activity concentrations of 137Cs, 241Am, 207Bi and 239+240Pu (up to 25,000 Bq/kg, 58 Bq/kg, 13 Bq/kg and 131 Bq/kg, respectively) and also high concentrations of organic matter (OM), comparing to other Scandinavian glaciers, reaching up ~40% of total mass. The outstandingly high concentrations of 137Cs, 241Am, Pu isotopes, and 207Bi on the Blåisen Glacier is primarily related to bioaccumulation of radionuclides in organic-rich cryoconite and might be enhanced by additional transfers of contamination from the tundra by lemmings during their population peaks. The presumed influence of intense rainfall on radionuclide concentrations in the cryoconite was not confirmed.